TRP drop, TRP drop: a steady patter of anti-schistosomal target illumination - Sprague, Daniel J.; Rohr, Claudia M.; Marchant, Jonathan S. (Frontiers in Parasitology, 2024)
Infections caused by parasitic flatworms impart a significant disease burden. This is well exemplified by the neglected tropical disease schistosomiasis, which afflicts millions of people worldwide. The anti-schistosomal activity of various chemotypes has been known for decades, but the parasite targets of many of these ligands remain undefined. Until recently, this included the current clinical therapy, praziquantel (PZQ). However, the tempo of target discovery has recently gathered pace, with discoveries of schistosome targets for praziquantel (PZQ) and the anthelmintic benzodiazepine, meclonazepam (MCLZ). This steady patter of target illumination has also revealed a pattern in that both PZQ and MCLZ target members of the same ion channel subgroup -transient receptor potential ion channels of the melastatin family (TRPM channels). PZQ activates one member of this family (TRPMPZQ) and MCLZ activates a different channel (TRPMMCLZ). Here, similarities and differences between these two new targets are discussed. These data highlight the need for further study of TRPM channels in parasitic flatworms given their vulnerability to chemotherapeutic attack.